“Just Another Little Black Boy From the South Side of Chicago”: Overcoming Obstacles and Breaking Down Barriers To Improve Diversity in the Law Professoriate - Green, Michael Z. (Columbia Journal of Gender and Law, 2015)
As I reflected on my personal experience to help address the persistence of discrimination in legal academia, I chose to focus on five areas of discussion for the open mic portion of the program held at the Association of American Law Schools Cross-Cutting Program, “The More Things Change . . . : Exploring Solutions to Persistent Discrimination in Legal Academia,” held on January 4, 2015, in Washington, D.C. First, I decided to address my personal development as an only child and male in a family of mostly black women struggling through the socioeconomic challenges of being poor and black. To add to that predicament and the narrative discussing it, I lived and grew up in one of this country’s most racially segregated cities in a community permeated with deadly criminal activities and hard core gangs. As an elementary school student, I lived on a block where people were stabbed, beaten, and killed. I saw people robbed and someone attempted to rob me at knifepoint in a violent confrontation. And those experiences still shape me today. Second, I decided to reflect on how core parental dedication helped to make sure that despite those surroundings I would be given a foundation to recognize that I could succeed and transcend the demoralizing pitfalls being observed on a daily basis in my neighborhood. Third, I must highlight how a lack of resources to adequately guide choices limits the pipeline possibilities even for those few like me who have the abilities to go forward. This discussion involves a lack of knowledge and financial support to even consider an Ivy League education and its benefits despite having the academic qualifications as a National Merit Finalist in high school. It also involves a discussion of being pushed to pursue a career in engineering when further reflection might have suggested development of other educational interests leading to a more traditional path in the law. Fourth, I have to bring forward my experience in recovering from a somewhat ill- advised engineering educational focus by going to law school which culminates with me obtaining a position in the academy as a law professor despite not having Ivy League credentials. The most important part of this discussion must include the support and the validation I received in my quest to join the professoriate that I gained by becoming a Hastie Fellow at the University of Wisconsin Law School. Finally, as an African American male who practiced employment discrimination law, worked at large law firms, a boutique, and a union law rm, and who now teaches and writes about issues of race and workplace discrimination, I believe that my personal experience adds a unique perspective especially given the dearth of African American male law professors who teach and write in an area of law so important to African American males. However, given the three minute timeframe during the actual presentation I only discussed the first two areas of focus: 1) the initial aspect of growing up in the Englewood neighborhood; and 2) how important parental involvement and activism was in pushing me forward despite the burdens of my surroundings. At the end of my presentation, I couched that discussion by asserting why I believed my story highlights how the lack of black male law professors who teach workplace law and discrimination supports the overall narrative of ongoing discrimination in the academy. The presentation and this Article reflect what it meant for me growing up under certain circumstances that presented barriers to becoming a law professor, and how that initial experience as shown by my personal narrative further indicates why discrimination in the academy continues.